2018
DOI: 10.1002/ece3.3851
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the energetic reward offered by field bean (Vicia faba) flowers: Nectar, pollen, and operative force

Abstract: Global consumption of crops with a yield that is dependent on animal pollinators is growing, with greater areas planted each year. However, the floral traits that influence pollinator visitation are not usually the focus of breeding programmes, and therefore, it is likely that yield improvements may be made by optimizing floral traits to enhance pollinator visitation rates. We investigated the variation present in the floral reward of the bee‐pollinated crop Vicia faba (field bean). We examined the genetic pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 55 publications
5
62
2
1
Order By: Relevance
“…Laboratory studies of consumption at the colony level have suggested a preference by workers for sugar concentrations of between 30 and 50%, when presented with choices ranging from 10 to 70% (Pouvreau 1974). In contrast, individual workers have been shown to prefer 60% over 45% concentrations, based on consumption (Konzmann and Lunau 2014), or 55% over 40%, with no differentiation between 55 and 68% when measured by number of visits (Bailes et al 2018). To our knowledge, the current study is the first to assess male preferences for different sugar concentrations, mimicking the variation in nectar quality they will experience under natural conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies of consumption at the colony level have suggested a preference by workers for sugar concentrations of between 30 and 50%, when presented with choices ranging from 10 to 70% (Pouvreau 1974). In contrast, individual workers have been shown to prefer 60% over 45% concentrations, based on consumption (Konzmann and Lunau 2014), or 55% over 40%, with no differentiation between 55 and 68% when measured by number of visits (Bailes et al 2018). To our knowledge, the current study is the first to assess male preferences for different sugar concentrations, mimicking the variation in nectar quality they will experience under natural conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies of workers have shown that they make clear foraging choices based on sugar concentration (e.g. Bailes et al 2018), which appear to trade-off choosing higher concentration sources versus the time taken to consume the nectar (which increases with concentration due to increases in viscosity ;Harder 1986). However, extrapolating from worker foraging preferences to the decisions that males may make is not straightforward, as workers are foraging for the colony, rather than just for themselves, and must also make trade-offs between nectar and pollen foraging (Konzmann and Lunau 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Previous work has shown that foraging worker bumblebees have a preference for nectars that contain 55% (wt/wt) sugar concentration (Bailes et al ., 2018). Critically, this sugar concentration falls within the range where the greatest drop in infection prevalence and intensity occurs in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional models of animal and human choice assume that individuals act to maximise the value they obtain from their choices (MacArthur & Pianka, 1966; Rapoport, 1989; Stephens & Krebs, 1986). For example, when presented with a set of otherwise identical options, honeybee colonies will choose the most concentrated sugar syrup (up to a threshold concentration; Bailes et al., 2018; Seeley et al., 1991) and female crickets will choose males with the highest chirp rate (Wagner & Reiser, 2000). These ‘single‐attribute’ decisions (where only one characteristic distinguishes options from one another) are often trivial to solve, as they only require the decision‐maker to compare options across a single factor of interest.…”
Section: Introductionmentioning
confidence: 99%